1983
DOI: 10.1021/bi00295a044
|View full text |Cite
|
Sign up to set email alerts
|

Order-disorder phase transition and lipid dynamics in rabbit small intestinal brush border membranes. Effect of proteins

Abstract: The total lipids extracted from brush border membranes form smectic lamellar phases when dispersed in water. 31P broad-band nuclear magnetic resonance (NMR) shows that between body temperature (37 degrees C) and freezing of the solvent, the extracted lipids form bilayers with the lipid molecules undergoing fast anisotropic motion. This is also true for the lipids present in the brush border membrane. The electron spin resonance (ESR) results obtained with various hydrophobic spin probes incorporated in either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The value of the activation energy E a ϭ 5.1 kcal/mol derived from the straight-line portion of the Arrhenius plot above 5°C (Fig. 3 B) agrees within the error of the measurement with the activation energy reported for the Na ϩ -dependent D-glucose transporter in the rat BBMVs (Brasitus et al, 1979) but is about half of the value reported by Mütsch et al (1983) for the same protein in rabbit BBM. The metal ion transport above the second break point is characterized by an activation energy of E a ϭ 14.8 kcal/ mol.…”
Section: Temperature Dependence Of Ni 2؉ Transportsupporting
confidence: 86%
See 3 more Smart Citations
“…The value of the activation energy E a ϭ 5.1 kcal/mol derived from the straight-line portion of the Arrhenius plot above 5°C (Fig. 3 B) agrees within the error of the measurement with the activation energy reported for the Na ϩ -dependent D-glucose transporter in the rat BBMVs (Brasitus et al, 1979) but is about half of the value reported by Mütsch et al (1983) for the same protein in rabbit BBM. The metal ion transport above the second break point is characterized by an activation energy of E a ϭ 14.8 kcal/ mol.…”
Section: Temperature Dependence Of Ni 2؉ Transportsupporting
confidence: 86%
“…The Arrhenius plot exhibits two break points, one at 5 Ϯ 1°C and another one at 24 Ϯ 1°C. Differential scanning calorimetry, electron spin resonance and fluorescence spectroscopy showed a broad gel-to-liquid crystal transition in both rat (Brasitus et al, 1980) and rabbit BBM (Mütsch et al, 1983). In the latter case this transition covers a temperature range from 10°C to 30°C (Hauser et al, 1982;Mütsch et al, 1983).…”
Section: Temperature Dependence Of Ni 2؉ Transportmentioning
confidence: 90%
See 2 more Smart Citations
“…2) as detected by independent physical measurements; rates of activity in the fluid phase markedly exceed those in the gel phase (Thilo et al 1977). A few examples include adenyl cyclase activity in plasma membranes of rat hepatocytes (Livingstone and Schachter 1980), glucose transport across brush border membranes of rabbit small intestine (Mutsch et al 1983), succinate oxidation in rat liver mitochondria (Raison et al 1971), and Na+ /H+ -exchange and water transport in human placenta (Illsley et al 1987). Perhaps related to the disruption of catalytic function, freeze-fracture electron micrographs reveal that upon phase separation, smoothfaced regions of the crystallized lipid domain are formed from which integral membrane proteins are excluded.…”
Section: Membrane Structure and Functionmentioning
confidence: 99%